(Undo revision 8335 by JulieDunbar (talk))
 
Line 4: Line 4:
  
 
$${ T }_{ ij }=\sum _{ ij }^{  }{ { e }^{ ij } } \left\lceil \ln { { X }_{ ij } }  \right\rceil$$
 
$${ T }_{ ij }=\sum _{ ij }^{  }{ { e }^{ ij } } \left\lceil \ln { { X }_{ ij } }  \right\rceil$$
 +
 +
$$sum_(i=1)^n i^3=((n(n+1))/2)^2$$

Latest revision as of 22:48, 30 August 2017

$$x = {-b \pm \sqrt{b^2-4ac} \over 2a}.$$

$$x=1a \over 2b$$

$${ T }_{ ij }=\sum _{ ij }^{ }{ { e }^{ ij } } \left\lceil \ln { { X }_{ ij } } \right\rceil$$

$$sum_(i=1)^n i^3=((n(n+1))/2)^2$$